2014
DOI: 10.1590/s0080-623420140000300012
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning of elderly with depressive symptoms

Abstract: Objective: To classify families of elderly with depressive symptoms regarding their functioning and to ascertain the presence of an association between these symptoms, family functioning and the characteristics of the elderly. Method: This was an observational, analytical, cross-sectional study performed with 33 teams of the Family Health Strategy in Dourados, MS. The sample consisted of 374 elderly divided into two groups (with and without depressive symptoms). The instruments for data collection were a socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 15 publications
(20 reference statements)
3
28
0
12
Order By: Relevance
“…Studies have reported that incidence of depression in older adults living in joint family system is lesser than those living in nuclear family. (7,9,12,15,16) Similar finding was observed in the present study. Good family support was found to be a protective factor against depression.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Studies have reported that incidence of depression in older adults living in joint family system is lesser than those living in nuclear family. (7,9,12,15,16) Similar finding was observed in the present study. Good family support was found to be a protective factor against depression.…”
Section: Resultssupporting
confidence: 91%
“…Activities of daily living were assessed using Katz Index of Independence in Activities of Daily Living (ADL) Scale. (11) Family care and Social interaction questions were adopted from an earlier study (12) and modified to local culture. Content validity was obtained from experts.…”
Section: Methodsmentioning
confidence: 99%
“…Family functioning is understood as a harmonic relationship and balance between the relationships of the family members, i.e., the way its members act together and with others. 13 Family support affects older age's ability to prevent stress and depression in their lives and improve functional abilities including cognitive abilities. 21 Family support is a form of servant behavior performed by the family both in the form of emotional support, award support, information support and instrumental support.…”
Section: Discussionmentioning
confidence: 99%
“…11 On the other hand, family is a social construct influenced by culture, historical context and relationships and, in general, is a synonym of affection, companionship and solidarity. 13 Family functioning is understood as a harmonic relationship and balance between the relationships of the family members, i.e., the way its members act together and with others. 13 Therefore, this study aimed to examine the relationships between personality, family support, and depression in elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Although for many students the university is the first experience of separation and living away from home, friends, romantic partners and familiar environment and for the first time students undertake complex obligations and responsibilities without direct help of their families (9), family functioning may have important role in students' depression. Family functioning is understood as a relationship and interaction between the family members (12) and it is considered as an important aspect of family environment that affect children physical, social and emotional health (13).…”
Section: Introductionmentioning
confidence: 99%